Venus's winds and temperatures during the MESSENGER's flyby: An approximation to a three‐dimensional instantaneous state of the atmosphere. Issue 8 (30th April 2017) - Peralta, J.; Lee, Y. J.; Hueso, R.; Clancy, R. T.; Sandor, B. J.; Sánchez‐Lavega, A.; Lellouch, E.; Rengel, M.; Machado, P.; Omino, M.; Piccialli, A.; Imamura, T.; et al.
Abstract : Even though many missions have explored the Venus atmospheric circulation, its instantaneous state is poorly characterized. In situ measurements vertically sampling the atmosphere exist for limited locations and dates, while remote sensing observations provide only global averages of winds at altitudes of the clouds: 47, 60, and 70 km. We present a three‐dimensional global view of Venus's atmospheric circulation from data obtained in June 2007 by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) and Venus Express spacecrafts, together with ground‐based observations. Winds and temperatures were measured for heights 47–110 km from multiwavelength images and spectra covering 40°N–80°S and local times 12 h–21 h. Dayside westward winds exhibit day‐to‐day changes, with maximum speeds ranging 97–143 m/s and peaking at variable altitudes within 75–90 km, while on the nightside these peak below cloud tops at ∼60 km. Our results support past reports of strong variability of the westward zonal superrotation in the transition region, and good agreement is found above the clouds with results from the Laboratoire de Météorologie Dynamique (LMD) Venus general circulation model. Plain Language Summary: The atmosphere of the Earth or Mars globally rotates with a speed similar to the rotation of the planet (approximately 24 h). The rotation of Venus is of about 243 days, much slower than the Earth, but when scientists measured the winds by tracking the clouds of Venus, they discovered that the atmosphere rotates 60 times faster! No one has explained yet what originates this "superrotation, " and we do not know well what happens either above or below the clouds. The technique of "Doppler shift" has been used to measure winds above the clouds, but results are "chaotic" and different to interpret. Thanks to a worldwide collaboration in June 2007 between NASA (MESSENGER), ESA (Venus Express), and many observatories (VLT in Chile, JCMT in Hawaii, HHSMT in Arizona, or IRAM in Spain), the authors combined the different data to obtain, for the first time, the instantaneous 3‐D structure of the winds on Venus at the clouds and also above, very important for new Venus models to start "forecasts" of the Venus weather with "data assimilation". We also discovered that the superrotation seems unexpectedly different on the night of Venus and that it varies its altitude depending on the day. Key Points: The 3‐D quasi‐simultaneous winds on Venus's day and night from combining space and ground observations We detect and quantify day‐to‐night and temporal wind changes between altitudes 50 and 120 km Comparison between wind data and GCM predictions indicates good agreement, but deviations occur at 60–70 km in nighttime